Pengaruh E-Service Quality Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi Pada Dompet Digital Dana (Studi Pada Pengguna Dana) - Novyantri, Rema; Setiawardani, Maya (International Journal Administration, Business & Organization, 2021)
This study aims to determine the effect of e-service quality on customer loyalty with satisfaction as a mediating variable. The population of this research is DANA users who have accessed and made transactions using DANA with a sample of 163 respondents. The data collection technique used a questionnaire with the validity and reliability test stages first. Data were analyzed using path analysis. The results of this study indicate that e-service quality affects DANA customer satisfaction, e-service quality affects DANA customer loyalty, customer satisfaction affects DANA customer loyalty, and customer satisfaction mediates the relationship between e-service quality and DANA customer loyalty.